Contribuição ao conhecimento químico de plantas do nordeste: Auxemma glazioviana Taub. (Boraginaceae) - Costa, José Galberto Martins da (2003)
This work describes the phytochemical analysis of the ethanol extract of the trunk heartwood and tnink barks of Auxemma glazioviana Taub. (Boraginaceae), popularly known as "pau-branco louro", collected in the locality Cristais and Quixadá - Ceará. This specie is largely used in civil constructions due to its wood resistence to fungi and termites and for the treatment of minor cut and wounds, as cicatrizant [...]